A Heart of Service: Discovering the Lived Experiences of Special Education Teachers Using Skill-Based Learning in Cebu City - Chua, Rikkie Nicole Dorothy; Egot, Hannah Xuchille; Espina, Daniel Andre; Forrosuelo, Ann; Gonato, Leah Fatima; Gungob, Alexandra Juliane; Habel, Valerie Shane; Devilleres, Rochelle Iah; Gagani, Flordeliza (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
Special education (SPED) learners often struggle in learning due to the curriculum and limited resources despite the awareness of the value of education globally. In the Philippines, inclusive education for all learners, especially for learners with special needs has yet to be delved deeper, hence, this study provides an exploration of the lived experiences of SPED teachers using skill-based learning to understand their perspectives of the participants on how this learning approach can help SPED learners acquire the skills needed for independence. Husserl’s descriptive phenomenological research design was used to describe the meaning of the lived experiences of the five SPED teachers using skill-based learning from Cebu City, Philippines. A semi-structured interview schedule served as the primary data collection instrument, supplemented by a focus group discussion to ensure data saturation. Colaizzi’s method of descriptive analysis was used to analyze the transcriptions, identifying key experiences, challenges, coping mechanisms, and meanings of teaching skill-based learning to SPED learners. Four major themes emerged from the analysis: Fulfillment in Teaching; Limited Resources, Parental Involvement, and Adjustment; Planning, Preparation, and Communication; and Emphasis on Practical Skills. Despite challenges, teaching SPED students could be fulfilling with passion and perseverance. The researchers recommend advocating for increased funding and programs to support SPED teachers in effectively implementing skill-based learning.